Analisis Pengaruh Profitabilitas, Leverage, Ukuran perusahaan dan Kepemilikan institusional terhadap Tax avoidance - maria denastri sarimin; Yunia Oktari (eCo-Fin, 2023)
This study aims to determine the effect of profitability, leverage, company size, and institutional ownership on tax avoidance. The population in this research is the financial statements of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. Sampling was carried out using the purposive sampling method with a sample of 22 companies during the observation period of 5 consecutive years so that the total sample was 110. The analysis of this study used the SPSS version 25 program with descriptive statistical tests, classical assumption tests, and hypothesis testing. The results of the research that have been processed show that the significant value of profitability with the ROA measuring tool is 0.407, the significant value of leverage with the DER measuring tool is 0.425, the significant value of firm size is 0.049, and the significant value of institutional ownership is 0.866. The results of this study prove that profitability has no significant effect on tax avoidance, leverage has no significant effect on tax avoidance, company size has a significant effect on tax avoidance, and institutional ownership has no significant effect on tax avoidance.